Impact of a Mobile Pharmaceutical and Healthcare Programme on Therapeutical Adherence in Heart Transplant P atients. (July 2018) - Gomis, Mar; Mangues, M.A.; Rodriguez, E.; De Pourcq, J.T.; Aretio, A.; Ferrero, A.; Brossa, V.; Lopez, L.; Mirabet, S.; Roig, E.
Abstract : Background and Objectives: Low therapeutical adherence (TA) to immunosuppressive drugs is one of the main factors that determine the survival of Heart Transplant (HT) patients. The aim of this study is to improve the TA of HT patients by means of a personalised care programme in a multidisciplinary environment, together with the support of mHeart platform. Materials and Methods: The mHeart platform is a healthcare tool designed to improve TA and consists of an App and a support web page. Currently, it is under a clinical trial (ID mHeart NCT02554578). This tool allows the patient to record timing of medication intake, complementary therapy, vital signs, side effects and symptoms, as well as facilitating communication with the multidisciplinary team. A prospective two-month study was carried out in a third-level hospital. All patients that had access to a mobile device and who had received CT in the past 18 months were included in the mHeart clinical trial. Personalised interventions both on-site and on-line via the mHeart platform, were performed with a view to improving TA. TA was assessed by means of validated tests applied during on-site visits scheduled at the beginning and end of the study (Haynes-Sackett y Morisky-Green). An independent statistician analysed the statistics using the IBM-SPSS (V22.0) Statistics pack. Results: Of the 35 patients (p) considered for inclusion, 32p (91.4%) were included in the study; 23p (71.9%) were men of an average age of 52.4 [42.9-63.7]. The follow-up time was 2.03 months [1.3-2.5]. With regard to polypharmacy, a median of 12 [8.5-14] different daily drugs was obtained, with 15 drugs being used in the case of 7p (22%). Other factors associated with lower TA were: patients' perception of taking too many drugs (17p) and patients feeling that taking their medication was highly inconvenient [4p (12.6%)] ;>8/10]. In relation to patients' choosing where to take their prescriptions, 27p (84.4%) stated that they regularly collected them from the same drugstore. TA during the first and last visit was 71.4%-89.3% according to the Haynes-Sackett TA test and 67.9%-85, 71% for Morisky-Green. In both cases, TA increases more than 17% (p>0.05). In both tests the final TA figure was over 85%, the target figure in solid organ transplants. With reference to the effectiveness of the pharmaceutical interventions, 6 to 8 patients (75%) who were nonadherent in the first visit, were adherent in the final visit according to Haynes-Sackett and 7 out of 9p (78%) in compliance with Morisky-Green. In both cases, >75% of the patients became adherent during the follow-up time. Conclusions: Obtaining information on how patients included in this study perceived the burden and inconvenience related to their medication, made the identification of patients at risk of low therapeutic adherence easier. The programme that was set up permits effective supervision of nonadherent patients, resulting in a clinically significant improvement in TA. This research study has been financed by Astellas Pharma and the General Pharmaceutical Council of Barcelona.